2013
DOI: 10.1007/s10409-013-0028-z
|View full text |Cite
|
Sign up to set email alerts
|

On aerodynamic noises radiated by the pantograph system of high-speed trains

Abstract: Pantograph system of high-speed trains become significant source of aerodynamic noise when travelling speed exceeds 300 km/h. In this paper, a hybrid method of non-linear acoustic solver (NLAS) and Ffowcs WilliamsHawkings (FW-H) acoustic analogy is used to predict the aerodynamic noise of pantograph system in this speed range. When the simulation method is validated by a benchmark problem of flows around a cylinder of finite span, we calculate the near flow field and far acoustic field surrounding the pantogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The aerodynamic noise of a fullscale DSA350 pantograph at 350 km/h was investigated numerically by Yu et al [83], using a hybrid method with FW-H acoustic analogy. They showed that the aerodynamic noise from the pantograph was generated by the flow separation, the unsteady wake and the strong interaction between components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aerodynamic noise of a fullscale DSA350 pantograph at 350 km/h was investigated numerically by Yu et al [83], using a hybrid method with FW-H acoustic analogy. They showed that the aerodynamic noise from the pantograph was generated by the flow separation, the unsteady wake and the strong interaction between components.…”
Section: Methodsmentioning
confidence: 99%
“…Yu et al [83] also considered the effect of a pantograph cover installed on the train roof numerically. They found that if the cover consists of only two sideward baffles it can reduce the noise by 3 dB by acting as a noise barrier.…”
Section: Roof-mounted Shieldsmentioning
confidence: 99%
“…Many important factors such as the elastic deformations of tracks and inter-vehicle interaction were ignored. For a better understanding of train derailment mechanism and dynamic derailment behavior, the existing models need to be further improved in the space scale of modeling trains coupled with tracks and the flexible modelling of their key components [27][28][29]. This paper presents a three-dimensional (3D) dynamic model of a highspeed train coupled with a flexible nonlinear track to carry out dynamic derailment analysis.…”
Section: Introductionmentioning
confidence: 98%
“…They found that insulators with elliptic cross sections whose long axis consists with the airflow direction are optimal. Yu et al [16] designed three kinds of pantograph guide guards and conducted a noise reduction analysis based on opened running mode of pantographs, finding that noise reduction effects were obvious and sound pressure levels were decreased by 3 dB adopting this pantograph guide guard similar to air barriers.…”
Section: Introductionmentioning
confidence: 99%